Communication from hieroglyphs to hyperlink - Platt, Richard; S. Adelstein(3,(BJonathans (Boston Kingfisher, 2004)
Explores the variety of ways in which humans communicate, including flags and fires, speech and writing, and through use of electronic media such as television and the internet
Includes index
11
Keywords: Communication -- Juvenile literature; Communication